Autopoetic Dynamics of the Illegal Logging System in Papua Forest - Sustyo Iriyono; Susanti Withaningsih; Budhi Gunawan; Johan Iskandar (Institut Pertanian Bogor (IPB University), 2023)
Illegal logging in Papua's forest areas has been a cause of unresolved degradation or deforestation and has developed into a complex problem. This study intends to elaborate on the complex dynamics of illegal logging in Papua, Indonesia, using Niklas Luhmann's Social System theory. The findings of this study are expected to provide a better understanding of the complexities of illegal logging and to encourage stakeholders to respond with more appropriate decisions and policies in accordance with their respective roles and authorities. The results of the research show that illegal logging in Papua is a social system that is formed from a simplification of the meaning of forests by actors who are purely economic-oriented. In facing the pressure from efforts to eradicate this system, the system has been reproducing in an autopoietic manner through differentiation to penetrate all other social systems pointed toward handling illegal logging and sustainable forest management, especially the law enforcement system and the customary forest community system. The ability of autopoietic to reproduce makes this system very flexible and cannot be handled by a rigid and bureaucratic system for dealing with illegal logging. It is suggested that the system for dealing with illegal logging must also be transformed into one of an autopoietic nature through collaborative management.